Geoquímica dos solos e das águas da Península Fildes e Ilha Ardley - Antártica Marítima - Renato Pereira de Andrade (2012)
To determine the composition of the water and the geochemical and mineralogical characterization of the soil from Peninsula Fildes (King George Island) and Island Ardley have a great importance. These islands in the Maritime Antarctica are the region of the biggest places of nidification (keeping birds) of penguins of the planet. Samples of superficial water were collected in 10 lakes and 13 meltwater channels and 84 soil samples in 28 profiles of depth in Fildes Peninsula and Island Ardley in the summer of 2008. In the water samples, the concentrations of major (Al, Ca, Fe, K, Mg, Na, Ti), minor and trace elements (As, Ba, Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb, Rb, Sr, V, Zn) and some anions (Cl- and PO43-) were measured using the techniques of HPLC, GF-AAS and ICP-MS. Concentrations of CHN, total Hg were determined in samples of soils by direct analysis of mercury (DMA), speciation by thermodesorption coupled to the atomic absorption (TDAAS) and sequential extraction procedure (Bloom et al., 2003). The concentrations of major (Al, Ca, Fe, K, Mg, Na, Ti), minor and trace elements (Co, Cu, La, Mn, Pb, S, Sr, Th, V and Zn) were measured by XRay Fluorescence (FRX). The mineralogical analysis was carried out by X-Ray Diffraction (XRD). Analysis of pH in water and Fe Mössbauer Spectroscopy in soil were also conducted. From the concentrations of major elements, it was calculated rates of weathering in the soils and the rate of enrichment for each element regarding a motionless element, in this study, Ti. In the case of the water, the results were in general similar to the ones obtained for Larsemann Hills fresh water lakes (Oriental Antarctic), for the McMurdos Dry Valleys, and Terra Nova Bay, except for the sample AM-29, for which higher concentrations were observed to As, Ca, Cr, Cu, Cl-, K, Mg, Mn, Na, PO43-, Rb, Se and Sr, what is explained by the proximity of the lake to the sea (20 m). Due to that, the penguins have a great influence on the input of these metals in the water. The variation observed in the samples of water is closely connected to geographical factors, like the distance from the sea, in other words, the entrance of the sea water in the Peninsula. The concentrations of the minor and trace elements of water samples with less sea influence are very low, suggesting an origin of natural sources, except for the elevated concentration of Pb (<LQ to 6,36 mg L-1). The values of the ratio Pb/Sr over the local average in specific areas close to the research stations indicates anthropic contamination, possibly originated from the burning of fossil fuels in the research stations. The Hg concentration present in soils had a variation from <4 to 256 ng.g-1, being the values found for the ornithogenic soils thehigher found in Antarctic soil. The high correlation of Hg with C points as important sources the guano and / or the birds' death /putrefaction, which are the local main sources of organic-matter (OM). The thermograms demonstrate that all the metal is in the form of Hg2+, when two types of connections with OM are found: one weaker, what is probably a physical retention, and a stronger one, which is possibly a complexation with organic matter. The results from chemical fragmentation indicated that most of the Hg is kept in OM. The percentage for the major elements in the soils was in general similar to the rates obtained for other soils of King George Island. However, there was an enrichment of P, Ca, Mg, K in the soils with influence of birds in the (ornithogenic) formation, regarding the soils without this sort of influence. This fact is the result from the addition of matter in the areas of nidification of penguins due to the deposition of a great quantity of excrements rich in those elements. The formation of the soils in whole studied region is predominantly by the physical disintegration of the rocks. The rates of chemical weathering (CIA, CIW and PIA) were low for all the soils, even with the mineralization of the OM originated from the guano and the pH lowering in the ornithogenic soils what did not result in an acceleration of the reactions of soil formations. The mineralogy of the soils is similar to the parental rock due to the low rates of weathering. The principal minerals found are the plagioclase (anorthite and albite), quartz, magnetite, pyroxene (augite) and argilominerals. The argilominerals from the chlorite and smectite classes were the predominant minerals detected in the totality of the profiles sampled both in Fildes Peninsula and in Ardley Island. In the ornithogenic profiles, in addition to the minerals originated from the parental rock, phosphates secondary minerals leuchophosphate and taranakita were detected in the places of ancient penguin colonies. In places of recent penguin colonies apatite, struvite and urates (salts derived from uric acid) were found. From the mineralogy data a qualitative scale of time was created to measure the age of ornithogenic soil formation. That scale is based on which are the phosphates minerals predominant in the soil. In the soils of active or recently abandoned penguin colonies, it was found basically phosphates of magnesium and phosphates of calcium which present more solubility (struvite and apatite). Minerals, predominantly iron phosphates aluminum phosphates and iron and aluminum phosphates, were found in long-time abandoned penguin colonies. Those phosphates are not very soluble (strengite, leuchophosphate and taranakite). The ascending order of soil age is related with the predominance of the following phosphate minerals: magnesium phosphates <calcium phosphates <aluminum phosphates <iron phosphates. This order was created based on the solubility: the higher the solubility, the smaller the time of permanency in the soil.